Two-dimensional gel electrophoresis analysis of the leiomyoma interstitial fluid reveals altered protein expression with a possible involvement in pathogenesis. - Ura, Blendi; Scrimin, Federica; Zanconati, Fabrizio; Arrigoni, Giorgio; Monasta, Lorenzo; Romano, Andrea; Banco, Rubina; Zweyer, Marina; Milani, Daniela; Ricci, Giuseppe (Oncol Rep, 2015)
Uterine leiomyoma is the most common smooth benign neoplasm. In the present study, we analyzed the global interstitial fluid (IF) profile of leiomyoma vs. normal myometrium to identify protein dysregulation involved in leiomyoma pathogenesis. Two-dimensional gel electrophoresis and mass spectrometry were used to generate and compare the global interstitial fluid profiles of the leiomyoma and of the normal tissue. Two proteins were validated by immunohistochemistry. By comparing the interstitial fluid profile of the leiomyoma with that of the normal myometrium, the levels of seven proteins were found to be significantly different: four structural organization proteins (desmin, prelamin-A/C, transgelin and α-actinin-1), an inflammatory response (α1-antitrypsin), a response to oxidative stress (peroxiredoxin-2), and a folding protein (heat shock 70 kDa protein 1A/1B). Desmin, α1-antitrypsin and peroxiredoxin-2 were upregulated in the leiomyoma, whereas heat shock 70 kDa protein 1A/1B, α-actinin-1, prelamin-A/C and transgelin were downregulated. Desmin and α1-antitrypsin were further validated by immunohistochemistry. By identifying proteins with altered expression levels compared to the myometrium from several pathways of the leiomyoma pathogenesis, we found the leiomyoma interstitial fluid to have a characteristic proteomic profile. A better appreciation of the pathophysiology of the disease can be useful in the development of conservative treatments that serve as viable alternatives to hysterectomy.

Effects of estroprogestins containing natural estrogen on vaginal flora. - De Seta, Francesco; Restaino, Stefano; Banco, Rubina; Conversano, Ester; De Leo, Rossella; Tonon, Maddalena; Maso, Gianpaolo; Barbati, Giulia; Lello, Stefano (Gynecol Endocrinol, 2014)
Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira®) in a quadriphasic regimen, while the other 30 women were administered 17-β estradiol with nomestrol acetate (EV+NOMAC - Zoely®) in a monophasic regimen. After a baseline study of vaginal milieu at recruitment of patients (Gram stain with Nugent score, vaginal pH, vaginal wet mount for the quantification of leukocytes, Lactobacilli and/or presence of Candida), we performed the same follow-up after six months of estroprogestin therapy. Our results showed that the women treated with E2V+DNG had a trend of an improvement of vaginal health in terms of increase of lactobacillar flora and reduction of vaginal pH in place of women treated with EV+NOMAC that showed a reduction of cervical mucus. Finally, our data about the effects on vaginal flora exerted by two estroprogestin pills (EPs) containing a natural estrogen suggest slight, but interesting differences in terms of vaginal ecology. These differences could be related to the type of estrogen, type of progestin, regimen of administration and, after all, to the net balance between estrogenic and progestin component of the EPs.
Keywords: Adolescent; Adult; Drug Combinations; Estradiol; Female; Humans; Megestrol; Middle Aged; Nandrolone; Norpregnadienes; Prospective Studies; Vagina; Young Adult

An unusual long-term complication of transobturator polypropylene mesh. - Sartore, Andrea; Zennaro, Floriana; Banco, Rubina (Arch Gynecol Obstet, 2014)
Serious complications associated with surgical mesh for transvaginal repair of POP, as infections, vaginal mesh exposure, painful mesh shrinkage and dyspareunia, are not rare. A 48-year-old woman underwent the Perigee procedure because of a stage 3 anterior wall prolapse. Eleven months after surgery, the patient became suddenly unable to walk because of a strong pain to the left thigh root after running. The MRI revealed an external obturator left muscle hyperintensity consistent with muscular oedema; the patient was treated with oral corticosteroids with a complete resolution of the pain. We could hypothesize that the posterior arm of the mesh caused a laceration of the muscles of the obturator space with consequent oedema and pain. The use of the meshes in prolapse surgery can cause unexpected long-term complications.
Keywords: Cystocele; Dyspareunia; Female; Glucocorticoids; Humans; Middle Aged; Pelvic Organ Prolapse; Polypropylenes; Postoperative Complications; Prednisone; Surgical Mesh; Treatment Outcome; Vagina

Effects of hormonal contraception on vaginal flora. - De Seta, Francesco; Restaino, Stefano; De Santo, Davide; Stabile, Guglielmo; Banco, Rubina; Busetti, Marina; Barbati, Giulia; Guaschino, Secondo (Contraception, 2012)
BACKGROUND: The sector of the market that deals with contraception offers a long list of different contraceptive methods. Within the estroprogestinic choice, the routes of administration are oral, transdermic and vaginal one. Even though efficacy is comparable with these methods, secondary and adverse effects are directly involved in the acceptability of the method. STUDY DESIGN: This was a prospective comparative study. During 1 year, we enrolled 60 asymptomatic women who voluntarily requested combined oral contraception (COC) or combined contraceptive vaginal ring (CCVR group). After a baseline study of vaginal milieu prior to starting hormonal contraception, we performed a follow-up. For each woman, we examined vaginal pH; quantification of leukocytes, lactobacilli, Candida and cocci on saline microscopy fluid; Gram stain with Nugent score and the presence of vaginal infection [culture for Trichomonas vaginalis, albicans and nonalbicans Candida, Group B Streptococcus (GBS)]. RESULTS: At the end of follow-up, there was a little change of vaginal milieu in both groups. We noted an increase of lactobacilli in the CCVR users and an increase of GBS in COC users. CONCLUSION: CCVR compared to COC users showed an increase of the number of lactobacilli in vaginal flora. It means that an increase of leukorrhea in that group could be protective in terms of prevention of vaginal imbalance/infection.
Keywords: Administration, Intravaginal; Adolescent; Adult; Bacterial Load; Candida; Candida albicans; Contraceptive Devices, Female; Contraceptives, Oral, Combined; Female; Humans; Hydrogen-Ion Concentration; Lactobacillus; Leukocyte Count; Middle Aged; Prospective Studies; Streptococcus agalactiae; Trichomonas vaginalis; Vagina